CUSTOMERS’ DECISION TO SAVE ON THE GOVERNMENT BANK: A CASE STUDY IN INDONESIA - Zulher; Ratnasih C. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
This study aimed to put forward the determination of the customer's decision to save the government banks. This study has been able to construct a theoretical model of the values contained in the quality of services and promotions in relation to the corporate image and the customer's decision to save. The results of the theoretical model explain that the values embodied in the quality of services and promotions directly affect the customer's decision to save and indirectly through the company's image influences customer’s decision to save. This study confirms the concept that corporate image affects the customer's decision to save. At the same time, the results of this study also revealed the importance of a bank to have a good quality service and conduct good promotional activities to customers to enhance the corporate image that will have an effect on improving the customer's decision to save in a banking company. In an effort to improve a customer's decision to save in all government bank branch officesthen employees should often make contact with customers such as giving notification of the latest promotions, the latest savings products and rising interest rates, so that it can increase the customer's decision to save.